Pengaruh Lingkungan Sosial terhadap Perilaku Menggunakan QRIS pada Generasi Z melalui Minat Menggunakan sebagai Variabel Mediasi - Amalia, Ivone (Konsumen & Konsumsi : Jurnal Manajemen, 2025)
Technological changes continue to change from year to year and are constantly updated. One of the technological changes that became a trend in Indonesia during the Covid 19 pandemic was the change in payment methods using QRIS. This study uses the UTAUT theory, which aims to analyze the effect of the Social Influence on Use Behavior QRIS through Intention to Use as a mediating variable. The method used in this research is quantitative method. Data is collected through questionnaires distributed online using Google Form through social media platforms such as X, Instagram Story, and WhatsApp. The sampling technique used is a purposive sample where the population is individuals who have used QRIS. The sample in this study is Generation Z aged 17-28 years and has used QRIS. This study uses SmartPLS as a tool to test and process data. The results of hypothesis testing can be said that the four hypotheses in this study are accepted. Intention to Use has an important role as a mediating variable. With social interaction and individual interest, it can make Generation Z adopt QRIS as a digital payment method. This research is expected to help other studies and become a reference and also useful for readers.